A systematic review and meta-analysis of the comparison of laparoscopic radiofrequency ablation to percutaneous radiofrequency ablation for hepatocellular carcinoma - Wang, Ya-Qiong; Tan, Zhen-Kun; Peng, Zha; Huang, Hai (Frontiers in Oncology, 2025)
BackgroundThe comparative evaluation of laparoscopic and percutaneous techniques for liver radiofrequency ablation remains unexplored. This study aims to determine the most effective ablation technique and patient selection for hepatocellular carcinoma (HCC) by analyzing the efficacy and safety of laparoscopic radiofrequency ablation (LRFA) versus percutaneous radiofrequency ablation (PRFA).MethodsTwo investigators (Y-QW and PZ) independently performed a literature search in the Cochrane Library, PubMed, Web of Science and Embase databases. Study quality was assessed using the Newcastle–Ottawa Scale or Cochrane risk-of-bias tool. Meta-analysis was conducted with Review Manager 5.4, applying either fixed- or random-effects models depending on study heterogeneity. The chi-square test (χ²) and I² statistics were employed for heterogeneity analysis.ResultsEight publications involving 1059 patients were included. Among them, 456 underwent LRFA and 603 underwent PRFA. LRFA showed a significantly better 3-year RFS than PRFA (OR: 1.89, 95% CI: 1.27-2.83, p = 0.002), the incidence rate of local recurrence was significantly fewer in the LRFA group (OR: 0.40, 95% CI: 0.23-0.69, p = 0.0010), but the postoperative hospital stay time was slightly shorter in the PFRA group (MD = 1.30; 95% CI 0.26 to 2.35; p=0. 01). Patients in the LRFA group had no significant difference in total postoperative complications, ablation success rates, overall survival (OS) and 1,5-year disease-free survival (DFS).ConclusionBoth LRFA and PRFA are effective treatments for HCC. LRFA shows better oncologic outcomes, including lower local recurrence and improved mid-term DFS. PRFA is simpler, less invasive and shorter hospital stays. The choice should be tailored to individual patient needs, considering tumor characteristics, comorbidities, and available expertise. Future research should focus on large-scale, prospective trials to validate these findings.Systematic review and registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024601797.